On Testing of Multiple Hypotheses of Continuous Probability Distributions Arranged into Two Groups - Yesayan, Aram O. (Mathematical Problems of Computer Science, 2023)
The optimal Neyman-Pearson procedure of detection is investigated for models characterized by four continuous probability distributions arranged into two groups considered as hypotheses. It is worthy to note that the case of three discrete probability distributions arranged in two groups was studied by Haroutunian and Yesayan in [1]. The Neyman-Pearson theorem holds immense importance when it comes to solving problems that demand decision making or conclusions to a higher accuracy.